Health and economic impact of the correct diagnosis of transthyretin cardiac amyloidosis in Spain. (3rd September 2021) - Formiga, Francesc; García-Pavía, Pablo; Martín Sánchez, Francisco Javier; Navarro-Ruiz, Andrés; Rubio-Terrés, Carlos; Peral, Carmen; Tarilonte, Patricia; López-Ibáñez de Aldecoa, Alejandra; Rubio-Rodríguez, Darío
ABSTRACT: Objective : To estimate the health and economic impact of the reduction in mortality and cardiovascular hospitalizations, associated with correct diagnosis of cardiac transthyretin amyloidosis (ATTR-CM), from the Spanish National Health System (NHS) perspective. Methods : A costs and effects analysis were performed (probabilistic Markov model) with time horizons between 1 and 15 years, comparing the correct diagnosis of ATTR-CM versus the non-diagnosis. Transition probabilities were obtained from the ATTR-ACT study (placebo arm) and from the literature. Costs and healthcare resources were obtained from Spanish sources (€ 2019) and from a panel of Spanish clinical experts. Results : After 1, 5, 10 and 15 years, the diagnosis of ATTR-CM would generate a gain of 0.031 (95%CI 0.025; 0.038); 0.387 (95%CI 0.329; 0.435); 0.754 (95%CI 0.678; 0.781) and 0.944 (95%CI 0.905; 0.983) life years per patient, respectively, with savings of € 212 (95%CI € −632; 633), € 2, 289 (95%CI € 2, 250; 2, 517), € 2, 859 (95%CI € 2, 584; 3, 149) and € 2, 906 (95%CI € 2, 669; 3, 450) per patient, respectively, versus the non-diagnosis. Conclusions : Just by correctly diagnosing ATTR-CM, years of life would be gained, cardiovascular hospitalizations would be avoided, and savings would be generated for the NHS, compared to the non-diagnosis of the disease.